Identification and Functional Analysis of Differentially Expressed Genes in Myzus persicae (Hemiptera: Aphididae) in Response to Trans-anethole. Issue 1 (27th December 2021) - Ding, Chao-Yang; Ma, Yu-Meng; Li, Bin; Wang, Yun; Zhao, Le; Peng, Jiang-Nan; Li, Mao-Ye; Liu, Su; Li, Shi-Guang
Abstract: Plant essential oils, with high bioactivity and biodegradability, provide promising alternatives to synthetic pesticides for pest control. Trans-anethole is the major component of essential oil from star anise, Illicium verum Hook. The compound has a strong contact toxicity against the green peach aphid, Myzus persicae (Sulzer) (Hemiptera: Aphididae), which is a major insect pest of many vegetables and crops. However, little information is known about how M. persicae responds to trans-anethole at the molecular level. We conducted a comparative transcriptome analysis of M. persicae in response to a LD50 dose of trans-anethole. A total of 559 differentially expressed genes were detected in the treated individuals, with 318 genes up-regulated, and 241 genes down-regulated. Gene ontology (GO) analysis revealed that these genes were classified into different biological processes and pathways. We also found that genes encoding ATP-binding cassette (ABC) transporters, DnaJ, and cuticle proteins were dramatically up-regulated in response to trans-anethole. To study the function of these genes, we performed RNA interference (RNAi) analysis. Knockdown of an ABC transporter gene ( ABCG4 ) and a DnaJ gene ( DnaJC1 ) resulted in a significantly increased mortality rate in M. persicae following trans-anethole exposure, indicating the involvement of these two genes in the toxicity response to trans-anethole. The findings provide new insights into the mechanisms of M. persicae in coping with plant essential oils.